2017
DOI: 10.1002/hup.2572
|View full text |Cite
|
Sign up to set email alerts
|

Repeated subcutaneous administrations of krokodil causes skin necrosis and internal organs toxicity in Wistar rats: putative human implications

Abstract: These findings contribute notably to comprehension of the local and systemic toxicological impact of this complex drug mixture on major organs and will hopefully be useful for the development of appropriate treatment strategies towards the human toxicological effects of krokodil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 55 publications
0
23
0
2
Order By: Relevance
“…Although heroin has been shown to cause oxidative stressinduced myocarditis, heroin did not affect the LV function in this AP4C -apical 4-chamber, AP2C -apical 2-chambers, SAX-B -short-axis basal, SAX-M -short-axis medial, SAX-A -short-axis apical study (16)(17)(18). Therefore, if there is no other risk factor to disrupt cardiac functioning (e.g., alcohol use), the use of heroin alone may not result in impairment of the LV function.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Although heroin has been shown to cause oxidative stressinduced myocarditis, heroin did not affect the LV function in this AP4C -apical 4-chamber, AP2C -apical 2-chambers, SAX-B -short-axis basal, SAX-M -short-axis medial, SAX-A -short-axis apical study (16)(17)(18). Therefore, if there is no other risk factor to disrupt cardiac functioning (e.g., alcohol use), the use of heroin alone may not result in impairment of the LV function.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, biochemical studies have shown creatine kinase, creatine kinase-MB, and uric acid changes. Significant alteration in the levels of reduced and oxidized glutathione in the kidney and heart suggest that oxidative stress may be involved in krokodil-mediated toxicity (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The impurities, particularly the high phosphorus concentrations of krokodil batches, may explain many of the signs and symptoms present in PWIK. 13 Besides pleasure, clinical cases related to PWIK and also animals exposed to krokodil suggest high pain tolerance to the corrosive and necrotizing effects. 13,14 Therefore, we hypothesized that, besides desomorphine, krokodil may uncover new morphinan derivatives capable of relieving moderate and severe pain and contribute to the addictive effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 Besides pleasure, clinical cases related to PWIK and also animals exposed to krokodil suggest high pain tolerance to the corrosive and necrotizing effects. 13,14 Therefore, we hypothesized that, besides desomorphine, krokodil may uncover new morphinan derivatives capable of relieving moderate and severe pain and contribute to the addictive effects. Aiming to identify additional morphinans (as a representative skeleton of a large class of opioids), a suitable analytical methodology, capable of identifying complex mixtures is required.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation